Constructing the image of the teacher on Reddit: Best and worst teachers. (May 2017) - Chang-Kredl, Sandra; Colannino, Daniela
Abstract: In addressing the public image of the teacher, this study reports on the analysis of 600 discussion entries on Reddit, a social media platform, in which respondents described memories of their best and worst teachers. Results of inductive analyses suggest: (1) a model of teacher, student, and teacher-student relationship for characterizing and reflecting on teachers in teacher education programs; (2) the relevance of social media in contributing to the public image of the teacher in an information technology age, as well as its anonymous and, arguably, more authentic nature; and (3) the need to address gender in teacher memory studies. Highlights: The influence of social media in constructing the public image of the teacher. Expanding reflective practices in teacher education. Addressing gender biases in teacher memory studies.